Eroded Rule of Law, Endemic Violence and Social Injustice in Brazil - Kovač, Mitja; Neves Bezerra Marcela (LeXonomica, 2020)
Modern Brazil is plagued by social and economic inequalities, endemic violence, crime, and a weak rule of law. Once these narratives become dependent on each other, all aspects must be worked on to change the scenario the country is facing: insecurity, fear and a lack of opportunities. This paper argues that the unprecedented rise of social injustice in Brazil is not the result of short-term measures but is part of its history marked by economic and social inequalities extending from its colonial past until today and the deficient policies on crime that emerged in the mid-1990s. Moreover, the current massive incarceration, overcrowding of prisons combined with the absence of human living conditions is turning the prison system in Brazil into a gigantic, perpetual school of crime. Investment in education that directly helps to lower the crime rate must be aligned with a new, less repressive and more inclusive punitive policy so as to induce criminals not to return to their unlawful ways. It is suggested that Brazil can only properly develop if efficient legal institutions, the rule of law, and criminal sanctioning based on the principles of social justice are available to all citizens.